دور مقرر مهارات الحاسوب المتقدم في تعديل الاتجاهات نحو تقنيات المعلومات والاتصالات لدى طلبة الدراسات العليا بكلية التربية جامعة تعز - الفقيه، عبدالباسط سعيد عبدالله; قطران، يحيى عبدالرزاق محمد (جامعة تعز فرع التربة - دائرة الدراسات العليا والبحث العلمي, 2021)
The study aimed at identifying the attitudes of postgraduate students towards information and communication technologies, and the role of the advanced computer skills course in modifying their attitudes and revealing the obstacles of their teaching. The study adopted the descriptive and quasi-experimental approaches, and its population consisted of 39 postgraduate students at the Faculty of Education in Taiz University. A scale of attitudes as well as a questionnaire were designed in order to reveal the differences between the two measurements. The major findings of the study revealed the absence of statistically significant differences attributed to the variables of gender and specialization, and the presence of a statistically significant effect between the mean scores of the pre and post measurements, in favor of the post measurement. The study also revealed several obstacles in studying the course like the absence of a teaching room equipped with essential facilities for practical training, low speed Internet connection, the insufficient time to apply the course related skills, as well as other obstacles in using information and communication technologies, most notably in e-learning. The study concluded with a number of recommendations and suggestions.
هدفت هذه الدراسة إلى معرفة اتجاهات طلبة الدراسات العليا نحو تقنيات المعلومات والاتصالات، ودور مقرر مهارات الحاسوب المتقدم في تعديل اتجاهاتهم، والكشف عن معوقات درستهم، واعتمدت الدراسة المنهجين الوصفي وشبه التجريبي، وتكون مجتمعها من طلبة الدراسات العليا بكلية التربية جامعة تعز، وعددهم (39) طالبا وطالبة، وقد أعد الباحثان أداتين (مقياسا للاتجاهات، واستبانة عن معوقات دراسة المقرر)، وطبقت الأداتان بعد دراسة المقرر؛ للكشف عن الفروق بين التطبيقين، القبلي والبعدي، وتوصلت الدراسة إلى نتائج من أهمها عدم وجود فروق دالة إحصائيا تعزي إلى متغيري النوع والتخصص، ووجود أثر دال إحصائيا بين متوسطي درجات التطبيقين القبلي والبعدي، يتجه نحو التطبيق البعدي، كما أشارت النتائج إلى وجود معوقات عدة عند دراستهم المقرر من أهمها، عدم توفر قاعة في الكلية مجهزة بالإمكانيات اللازمة للتدريب على مهارات المقرر، وضعف شبكة الإنترنت، وقلة المدة المتاحة لتطبيق مهارات المقرر، فضلا عن وجود معوقات أخري في توظيف تقنيات المعلومات والاتصالات؛ أبرزها ضعف إمكانيات تطبيق التعليم الإلكتروني، وقد انتهت الدراسة بالتوصيات والمقترحات اللازمة.
Keywords: المهارات الحاسوبية -- تقنيات المعلومات -- طلبة الدراسات العليا